Renal bicarbonate reabsorption in the rat. I. Effects of hypokalemia and carbonic anhydrase. - Capasso, G (1986)
Free-flow micropuncture studies were carried out on superficial rat proximal and distal tubules to assess the participation of different nephron segments in bicarbonate transport. Particular emphasis was placed on the role of the distal tubule, and micro-calorimetric methods used to quantitate bicarbonate reabsorption. Experiments were carried out in control conditions, during dietary potassium withdrawal, and after acute intravenous infusions of carbonic anhydrase. We observed highly significant net bicarbonate reabsorption in normal acid-base conditions as evidenced by the maintenance of significant bicarbonate concentration gradients in the presence of vigorous fluid absorption. Distal bicarbonate reabsorption persisted in hypokalemic alkalosis and even steeper transepithelial concentration gradients of bicarbonate were maintained. Enhancement of net bicarbonate reabsorption followed the acute intravenous administration of carbonic anhydrase but was limited to the nephron segments between the late proximal and early distal tubule. The latter observation is consistent with a disequilibrium pH along the proximal straight tubule (S3 segment), the thick ascending limb of Henle, and/or the early distal tubule.